2019
DOI: 10.5603/ep.a2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and temozolomide combination for treatment of high-grade, well-differentiated neuroendocrine tumour and poorly-differentiated neuroendocrine carcinoma — retrospective analysis

Abstract: Introduction: Many retrospective studies have confirmed that capecitabine combined with temozolomide is effective in neuroendocrine neoplasms. Most of the studies focused on grade 1 and grade 2 neuroendocrine tumours, mainly of pancreatic origin. There are limited data regarding the efficacy capecitabine with temozolomide in grade 3 neuroendocrine tumours. The new World Health Organisation 2017 classification distinguished well-differentiated grade 3 neuroendocrine tumours from poorly differentiated grade 3 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
2
29
1
6
Order By: Relevance
“…Only 16 were evaluable for radiological response and DCR was 38%, while no PR or CR were observed. Efficacy of temozolomide plus capecitabine was further assessed[52] in patients with GEP-NET G3 (n=20) and GEP-NEC G3 (n=12). DCR was 70% in the NET group and 30% in NEC group.…”
mentioning
confidence: 99%
“…Only 16 were evaluable for radiological response and DCR was 38%, while no PR or CR were observed. Efficacy of temozolomide plus capecitabine was further assessed[52] in patients with GEP-NET G3 (n=20) and GEP-NEC G3 (n=12). DCR was 70% in the NET group and 30% in NEC group.…”
mentioning
confidence: 99%
“…A NET G2-like medical treatment strategy as tested in recent small retrospective studies may be more appropriate for patients with NET G3. Temozolomide/ capecitabine in patients with NET G3 tumors resulted in a disease control rate of 70%, PFS 15 months and OS 22 months (Rogowski et al 2019). Everolimus in patients with pancreatic NET G3 with a Ki-67 ≤55% resulted in a PFS of 6 months and OS of 28 months (Panzuto et al 2017).…”
Section: R69 H Sorbye Et Almentioning
confidence: 99%
“…The patient was initially treated with systemic chemotherapy utilizing capecitabine 1500 mg/m 2 po BID D1-14 and temozolomide 150 mg/m 2 D10-14 every 28 days [ 2 ]. Imaging studies after 4 cycles of chemotherapy showed interval progression of the disease with development of numerous liver lesions and increased size of peritoneal masses.…”
Section: Case Presentationmentioning
confidence: 99%
“…It was previously known as clear cell sarcoma-like tumor of the GI tract (CCSLTGT) [ 1 ]. In the recent years, it has been recognized as a separate entity with specific histologic, immunohistochemistry, and molecular features [ 2 ]. GNET carries a poor prognosis, and systemic therapeutic options are very limited with lack of guidelines or management recommendation.…”
Section: Introductionmentioning
confidence: 99%